Evaluation of Strawberry Seedling Growth in Various Planting Media Amended with Biofertilizer - Hindersah, Reginawanti; Purba, Putri S.J.; Cahyaningrum, Diana N.; Nurbaity, Anne; Kamaluddin, Nadia N.; Akutsu, Masako (KnE Life Sciences, 2022)
The quality of strawberry seedlings is impacted by the composition of the growing medium. Due to its good drainage and high water-holding capacity, coco-peat is now widely used as a major component of strawberry substrate; however, coco-peat has a low nutrient content. By combining coco-peat with manure and biofertilizer, more nutrients can be provided. This study investigated the effect of the growing medium composition with biofertilizer inoculation on the growth and quality of strawberry seedlings in a mountainous area using a pot experiment. With six treatments and five replications, the experiment was set up in randomized block design. The treatments involved substrate composition, which included cocopeat and chicken manure in ratios of 2:1, 2:3 and 3:2, and biofertilizer inoculation (with and without). Nitrogen-fixing bacteria and phosphate-solubilizing microbes were included in the biofertilizer. The results showed that substrate composition affected plant height, shoot and root dry weight, chlorophyll content, and nitrogen and phosphorus uptake by seedling shoots, but not the surface area of leaves on six-week-old seedlings. The addition of biofertilizer to substrates made up of cocopeat and chicken manure in ratios of 2:3 and 3:2 increased plant growth and nitrogen and phosphorus uptake. Keywords: Chicken namnure, Cocopeat, N2 -fixer bacteria, P-solublizer Microbes.